The Impact of Transformational Leadership on Educational Environments: A Systematic Review - Yoserizal; Darmayanti, Rina; Septrisia, Reni; Rusdinal; Hadiyanto; Rifma (Mimbar Ilmu, 2024)
School principals play a central role in shaping the educational environment through the policies they implement. Transformational leadership by school principals focuses on empowering teachers, enhancing student motivation, and fostering a positive school culture to achieve better educational outcomes. This study aims to provide a systematic literature review of the impact of transformational leadership by school principals on the educational environment. The research reviews relevant articles published in the past five years from the Scopus and ERIC databases, using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. The findings of this study show that the majority of research focuses on the junior high school level, which is considered a critical transitional phase for students. Transformational leadership by school principals can improve teacher performance in areas such as creativity, innovation, and self-efficacy, which in turn contribute to student learning outcomes. Moreover, successful strategies employed by school principals include creating a conducive school climate, enhancing collaboration among teachers, strengthening relationships with parents, and fostering a positive school culture. These findings conclude the necessity of involving all elements within the educational environment to create an ecosystem that supports the holistic development of students.